Researches and developments on production of Ni-W alloy based substrates for second generation high-temperature superconductors - Finkel, V.A.; Bovda, A.M.; Derevyanko, V.V.; Leonov, S.A.; Sungurov, M.S.; Sukhareva, T.V.; Khoroshikh, V.M.; Shakhov, Yu.N. (Functional Materials, 2012)
The possibilities to prepare high quality substrates for second generation high temperature superconductors based on Ni—W alloys in the 0-9.5 at. % W concentration range was studied. Researches and developments were carried out in the following directions: a) Ni—W alloy synthesis; b) preparation of Ni—W alloy tapes by rolling with subsequent heat treatment; c) coating the tape by TiN layer. For the first time, the possibility was established to obtain the {001} <100> cubic texture favour to YBa₂Cu₃O₇₋₈ superconductor subsequent epitaxial growth on the high W paramagnetic Ni—W tape surface by varying the regimes of TiN deposition.